PENERAPAN NILAI KARAKTER DALAM KEGIATAN KEPRAMUKAAN DI SEKOLAH DASAR - Nurhayati Nurhayati; Muhlis Madani; Syarifuddin Sida (Universitas Pakuan, 2021)
APPLICATION OF CHARACTER VALUES IN SCOUTING ACTIVITIES IN ELEMENTARY SCHOOLS Abstract. This study aims to: (1) find out the application of character values in scouting activities at primary school, (2) find out what factors influence the application of character values in scouting activities at Primary school, and (3) find out whether activities Scouts improve the character of the students of primary school. This study uses a qualitative approach. The data in this study were obtained through observation, in-depth interviews, and documentation with interactive model data analysis. The results showed that the application of character values in scouting activities at primary school was adjusted to the values of character education according to Listyarti (2012), namely: (1) religious, (2) honest, (3) tolerance, (4 ) discipline, (5) hard work, (6) creative, (7) independent, (8) democratic, (9) curiosity, (10) national spirit, (11) love for the homeland, (12) respect for achievement, (13) friendly/communicative, (14) peace-loving, (15) likes to read, (16) cares about the environment, (17) cares about social, and (18) is responsible. Meanwhile, factors that affect the application of the character values in scouting activities in primary school, namely: First, the supporting factors, namely the implementation of the mandate of Act No. 12 of 2010 concerning the Scouting movement and Decision Munas results of the Scout Movement in 2013. The second, factor barriers, namely funding, and the relatively low level of parental knowledge about Scouting activities so that parents are less motivated to actively participate in Scouting activities. Scout activities carried out primary school improve the character of students. This can be seen in the results of the study where 18 values of character education are always taught by the coach/teacher in scout extracurricular activities. In addition, giving examples of good attitudes, which contain character values through scouting materials also makes students more behave and act according to directions or rules.